Penerapan Media Komik untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran IPA di SD Negeri 006 Rambah Samo - Retno Wulan, Rinjani; Hasibuan, Abdul Putra Ginda; Efendi, Rinja; Marta, Eni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research was motivated by the problems that occurred at SD Negeri 006 Rambah Samo, namely the scores obtained by students were still far from the KKM set. This study aims to determine the application of comic media to increase student learning motivation in science subjects at SD Negeri 006 Rambah Samo. This research is classroom action research. The subject of this study is all students of grade V of SD Negeri 006 Rambah Samo totaling 22 people. This research consists of two cycles. Data collection using interviews and documentation. The results of the research showed that the desire and desire succeeded in the initial condition was 43.21%, the first cycle was 69%, the second cycle was 75.28%. the existence of encouragement and need in learning was 49.52%, cycle I was 72.5%, cycle II was 85.2%, there were hopes and ideals of 51.60%, cycle I was 77%, cycle II was 80%, reward activities in learning were 53.57%, cycle I was 75.28%, cycle II was 85%, interesting activities in learning was 49.28%, cycle I was 70.85%, cycle II was 90%. In the initial condition, the number of students who reached KKM was 10 people, in the first cycle there were 12 students and in the second cycle there were 22 students. In cycle II, student motivation has reached the indicator. It can be concluded that the application of comic media can increase students' motivation to learn